THE HIGHWAY AND ECONOMY DEVELOPMENT A HISTORICAL STUDY OF THE DEVELOPMENT OF ECONOMICAL KNOTS AT THE NORTH COASTAL OF JAVA (PANTURA) IN 1930S - 1980S - Hartatik, Endah Sri (Paramita: Historical Studies Journal, 2018)
This article analyze the relationship between Pantura (the north coastal) highway in Central Java and the economy development society in those areas at the Dutch Colonial era. The Dutch Colonial on the land transportation, especially in highway could open an opportunity for the development of industries sector. In the north coastal of Java, some cities emerged, such as Semarang, Pekalongan and Kudus. Those industrial cities became a magnet for urban people to appear. They came to those cities for venturing as industrial laborers, construction workers, blue-collar workers, such as housemaids, porters in terminal, market and harbor. The better highway, the increase of factory production, and the provided workers led the cities from Tegal to Semarang being the developed cities which never slept for 24 hours because they were a main road of goods transportation from the producers to the consumers. Thus, this condition caused an adequate high mobility in the areas.Ã‚Â Artikel ini menganalisis hubungan antara jalan raya Pantura (pesisir utara) di Jawa Tengah dan masyarakat pengembangan ekonomi di daerah-daerah di era Kolonial Belanda. Kolonial Belanda pada transportasi darat, terutama di jalan raya bisa membuka peluang bagi pengembangan sektor industri. Di pesisir utara Jawa, beberapa kota muncul, seperti Semarang, Pekalongan dan Kudus. Kota-kota industri tersebut menjadi magnet bagi masyarakat urban untuk tampil. Mereka datang ke kota-kota tersebut untuk menjelajah sebagai buruh industri, pekerja konstruksi, pekerja kerah biru, seperti pembantu rumah tangga, kuli di terminal, pasar dan pelabuhan. Jalan raya yang lebih baik, peningkatan produksi pabrik, dan pekerja yang diberikan membawa kota-kota dari Tegal ke Semarang menjadi kota maju yang tidak pernah tidur selama 24 jam karena merupakan jalur utama transportasi barang dari produsen ke konsumen. Dengan demikian, kondisi ini menyebabkan mobilitas tinggi memadai di daerah.Ã‚Â